2012
DOI: 10.1371/journal.pone.0046230
|View full text |Cite
|
Sign up to set email alerts
|

Flt3L Combined with Rapamycin Promotes Cardiac Allograft Tolerance by Inducing Regulatory Dendritic Cells and Allograft Autophagy in Mice

Abstract: The induction of immune tolerance is still a formidable challenge in organ transplantation. Dendritic cells (DCs) play an important role in orchestrating immune responses by either mediating protective immune responses or inducing antigen specific tolerance. Previous studies demonstrated that the fms-like tyrosine kinase 3 receptor (Flt3) and its ligand (Flt3L) play an essential role in the regulation of DC commitment and development. Here, we report a synergic effect between Flt3L and low-dose rapamycin (Rapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Interestingly, others found that rapamycin and Flt3L could be combined to improve engraftment of cardiac allografts in mice. 38 Consistent with our findings, these authors also noticed an increase in pDC and Treg frequencies (without however further addressing the underlying mechanism). 38 These data illustrate the wide range of potential applicability of the Flt3L/rapamycin combination.…”
Section: Implications For Immune Tolerance Therapysupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, others found that rapamycin and Flt3L could be combined to improve engraftment of cardiac allografts in mice. 38 Consistent with our findings, these authors also noticed an increase in pDC and Treg frequencies (without however further addressing the underlying mechanism). 38 These data illustrate the wide range of potential applicability of the Flt3L/rapamycin combination.…”
Section: Implications For Immune Tolerance Therapysupporting
confidence: 91%
“…38 Consistent with our findings, these authors also noticed an increase in pDC and Treg frequencies (without however further addressing the underlying mechanism). 38 These data illustrate the wide range of potential applicability of the Flt3L/rapamycin combination. Conversely, these findings have implications for immunotherapy, as discussed previously for breast cancer.…”
Section: Implications For Immune Tolerance Therapysupporting
confidence: 91%
See 1 more Smart Citation
“…Total proteins were extracted from cardiac allograft and subjected to immunoblots assay as described previously . The primary antibodies used in the study include rabbit anti‐HMGB1 (Abcam, Cambridge, MA, USA) and rabbit anti‐GAPDH (Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This effect appears to be mediated via the selective expansion of ‘tolerogenic’ pDCs . Moreover, a combination of rapamycin and Flt3L promotes organ allograft survival in mice by inducing regulatory DC and allograft autophagy . Myeloid‐derived suppressor cells (MDSCs) …”
Section: Molecular Biology Of Mtorcsmentioning
confidence: 99%